Genetic Ablation of CXCR2 Protects against Cigarette Smoke-Induced Lung Inflammation and Injury - Lerner, Chad A.; Lei, Wei; Sundar, Isaac K.; Rahman, Irfan (Frontiers in Pharmacology, 2016)
Antagonism of CXCR2 receptors, predominately located on neutrophils and critical for their immunomodulatory activity, is an attractive pharmacological therapeutic approach aimed at reducing the potentially damaging effects of heightened neutrophil influx into the lung caused by environmental agents including tobacco smoke. The role CXCR2 in lung inflammation in response to cigarette smoke (CS) inhalation using the mutant mouse approach is not known. We hypothesized that genetic ablation of CXCR2 would protect mice against CS-induced inflammation and DNA damaging response. We used CXCR2 -/- deficient/mutant (knock-out, KO) mice, and assessed the changes in critical lung inflammatory NF-B-driven chemokines released from the parenchyma of CS-exposed mice, and indications of the extent of tissue damage assessed by the number of DNA damaging γH2AX positive cells. CXCR2 KO mice exhibited protection from heightened levels of neutrophils measured in BALF taken from mice exposed to CS. IL-8 (KC mouse) levels in the BALF from CS-exposed CXCR2 KO were elevated compared to WT. IL-6 levels in BALF were refractory to increase by CS in CXCR2 KO mice. There were no significant changes to MIP-2, MCP-1, or IL-1β. Total levels of NF-κB were maintained at lower levels in CS-exposed CXCR2 KO mice compared to WT mice exposed to CS. Finally CXCR2 KO mice were protected from increased number of lung cells positive for DNA damage response and senescence marker γH2AX, CXCR2 KO mice are protected from heightened inflammatory response mediated by increased neutrophil response as a result of acute 3 day CS exposure. This is also associated with changes in pro-inflammatory chemokines and reduced incursion of γH2AX indicating CXCR2 deficient mice are protected from lung injury. Thus CXCR2 may be a pharmacological target in setting of inflammation and DNA damage in the pathogenesis of COPD.